2015
DOI: 10.1016/j.livsci.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile in zebu dairy cows (Bos taurus indicus) with mastitis caused by Streptococcus agalactiae

Abstract: a b s t r a c tMastitis is an inflammatory response in the mammary gland caused by an influx of somatic cells, composed mainly of neutrophils, macrophages and lymphocytes. The speed and efficacy of the host's immune response to the invasive pathogen affects the establishment, persistence and severity of the infection. To characterize the gene expression and response mechanism to infection by Streptococcus agalactiae (S. agalactiae) in zebu dairy cows of the Gyr breed, we carried out a transcriptome study of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
(82 reference statements)
1
13
0
Order By: Relevance
“…These results are in accordance with findings of Fonseca et al . (2015) who showed that CCL2 was up-regulated in milk samples after inoculation with the same strain in the udders. Similarly to our results, only a few studies demonstrated that the chemokine CCL5 (also known as RANTES) is strongly expressed in the infected udder as well as in inflammation stimulated MEC (Günther et al ., 2009, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results are in accordance with findings of Fonseca et al . (2015) who showed that CCL2 was up-regulated in milk samples after inoculation with the same strain in the udders. Similarly to our results, only a few studies demonstrated that the chemokine CCL5 (also known as RANTES) is strongly expressed in the infected udder as well as in inflammation stimulated MEC (Günther et al ., 2009, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the transcriptional profile of bovine mammary tissue after challenge with S. agalactiae is poorly characterized. Only a few studies have investigated the changes in gene expression in milk samples after IMI with S. agalactiae (Fonseca et al ., 2011, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations